2007
DOI: 10.1111/j.1600-0633.2007.00258.x
|View full text |Cite
|
Sign up to set email alerts
|

Invasive molluscs in the diet of Pterodoras granulosus (Valenciennes, 1821) (Pisces, Doradidae) in the Upper Paraná River floodplain, Brazil

Abstract: Diet composition of Pterodoras granulosus was investigated from June 2004 to June 2005 in the Upper Paraná River floodplain, following invasion by two mollusc species Corbicula fluminea and Limnoperna fortunei. Stomach and intestinal contents analysis showed spatial differences in the diet composition. In the Baía River, P. granulosus diet consisted mainly of C. fluminea, whereas plant items dominated in the Ivinheima River, and L. fortunei was the most important food in the Paraná River. There was little sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
1
8

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 10 publications
0
30
1
8
Order By: Relevance
“…Trough predation, I. labrosus may represent a natural and abundant predator of these two harmful species of freshwater ecosystems, and could play an important role in terms of controlling dispersion ranges of these Bivalvia species. One the other hand, I. labrosus may act as disperser in case bivalves survive to the digestion (Cantanhêde et al, 2008). In this study, however, most of these bivalves were found broken and totally digested.…”
Section: Dietcontrasting
confidence: 47%
“…Trough predation, I. labrosus may represent a natural and abundant predator of these two harmful species of freshwater ecosystems, and could play an important role in terms of controlling dispersion ranges of these Bivalvia species. One the other hand, I. labrosus may act as disperser in case bivalves survive to the digestion (Cantanhêde et al, 2008). In this study, however, most of these bivalves were found broken and totally digested.…”
Section: Dietcontrasting
confidence: 47%
“…Fish have been reported to consume these mollusks, particularly the Doradidae Pterodoras granulosus, whose diet contains large amounts of C. fluminae and L. fortunei (Ferriz et al 2000;Gaspar da Luz et al 2002;Cantanhêde et al 2008). Although the eradication of aquatic invasive species is a difficult task (Vitule et al 2009), it is expected that intensive consumption can have an important role in their control.…”
Section: Diet Compositionmentioning
confidence: 99%
“…empty shells provide substrate or refuge for algae, gastropods, freshwater sponges, or other benthic species) (Crooks 2002, Gutiér-rez et al 2003 and be a new food resource for several pelagic and benthic species (Cantanhêde et al 2008). Species from higher trophic levels are expected to consume C. fluminea and its high abundance and biomass may be a very important food source in many aquatic ecosystems.…”
Section: Possible Ecological Effectsmentioning
confidence: 99%